A Novel Ag@AgCl Nanoparticle Synthesized by Arctic Marine Bacterium: Characterization, Activity and Mechanism - Shuang Li; Hui Zhang; Bailin Cong; Peiqing He; Wenqi Liu; Shenghao Liu (International Journal of Molecular Sciences, 2022)
An additive- and pollution-free method for the preparation of biogenic silver and silver chloride nanoparticles (Ag@AgCl NPs) was developed from the bacteria Shewanella sp. Arc9-LZ, which was isolated from the deep sea of the Arctic Ocean. The optimal synthesizing conditions were explored, including light, pH, Ag+ concentration and time. The nanoparticles were studied by means of ultraviolet-visible (UV-Vis) spectrophotometry, energy dispersive spectrometry (EDS), X-ray diffraction (XRD) and inductively coupled plasma optical emission spectrometers (ICP-OES). The transmission electron microscope (TEM) showed that the nanoparticles were spherical and well dispersed, with particle sizes less than 20.00 nm. With Ag@AgCl nanoparticles, the kinetic rate constants for congo red (CR) and rhodamine B (RhB) dye degradation were 2.74 × 10−1 min−1 and 7.78 × 10−1 min−1, respectively. The maximum decolourization efficiencies of CR and RhB were 93.36% and 99.52%, respectively. Ag@AgCl nanoparticles also showed high antibacterial activities against the Gram-positive and Gram-negative bacteria. The Fourier transform infrared spectroscopy (FTIR) spectrum indicated that the O-H, N-H and -COO- groups in the supernatant of Arc9-LZ might participate in the reduction, stabilization and capping of nanoparticles. We mapped the schematic diagram on possible mechanisms for synthesizing Ag@AgCl NPs.